Freezing of a nanofluid droplet : from a pointy tip to flat plateau - Zhao, Yugang (2021)
Understanding the dynamics during freezing of nanofluid droplets is of importance from both fundamental and practical viewpoints. It is known that a universal pointy tip is formed on the top of a frozen water droplet [Marín et al., Phys. Rev. Lett. 113(5), 054301 (2014)]. Here, we report that the formation of a pointy tip is broken down due to the presence of nanoparticles; instead, the top of a frozen nanofluid droplet exhibits a flat plateau shape and such a plateau becomes larger at higher particle concentrations. We show that the phenomenon of such shape changes in freezing nanofluid droplets is universal, independent of contact angle, droplet volume, particle size, and particle material. We propose an analytical model to attribute the plateau formation to a capillary driven compensating flow due to segregated particles moving along the freezing interface.